Kebutuhan Regulasi bagi Pembentukan Kelompok Pengelola Desa Ekowisata Bukit 7 Sempan - A. Cery Kurnia; Sintong Arion Hutapea; Toni Toni; Muhammad Qomaruddin Ridwan (UNES Law Review, 2023)
This research is based on the fact that in Sempan Village there is have potential eco tourism for Bukit 7 Sempan which requires professional institutions. However, there is a void in the legal basis for the Sempan Village Government in creating institutional governance. This research was written using an empirical normative approach that relies on secondary data and primary data. The role of the village is part of the constitutional aspect because the village is an autonomous government unit. Village government is indeed a part that cannot be separated geographically because the village government area is also a regional government area. But uniquely, on the one hand, the village also always has its autonomy, namely in terms of controlling the village household and making village regulations. The village is a self-governing community, a form of autonomy from the Sempan Village Government in managing Sempan 7 Hill is by forming a Tourism Awareness Group (Pokdarwis). Efforts to guarantee legal certainty. By giving Pokdarwis legality, it will enjoy a position like other legal subjects.